Study of Carbon Emissions Due to Changes in Land Use in Bontang City, East Borneo - Princes, Kathlyne Septrilisia; Arifin , Moch; Priyadarshini, Rossyda (Future Science, 2023)
Forests are a store of carbon stocks, carbon is transferred from the atmosphere into the plant body through the process of photosynthesis. The occurrence of land conversion and land cover changes can cause the loss of carbon stocks, causing global warming. This study aims to identify changes in carbon stocks (C) due to land use change, as well as carbon emissions caused by the use of industrial forest land, dry land, and horticultural land in Bontang City, the part of East Borneo. Carbon stock in land consists of several components, namely soil carbon, top plant carbon, bottom plant carbon, litter carbon, and necromass carbon. The measurement results show that the largest carbon stock value is found in industrial forest land type 2 with a value of 158.54ton/ha. Carbon emissions occurred in the period 2009 to 2016 on forest land that was turned into type 1 industrial forest land, moor, and horticulture. The carbon emission that occurs is 34.09kton.